PROSEDUR DAN METODE PENERJEMAHAN BAHASA SLANG DALAM KOMIK CRAYON SHINCHAN KARYA YOSHITO USUI - Dewi Octaviani, Eka (Humanis; Volume 15. No.2. Mei 2016, 2016)
The title of this research is “The Translation Procedure and Method of Slang Language in Crayon Shinchan by Yoshito Usui”. This research describes category and frequency of occurrence of slang language and the translation procedures and methods which applied on translating Crayon Shinchan from Japanese language into Indonesian language. The theories used in this research are slang language theory according to Yonekawa (2003) and translation procedure according to Vinay and Darbelnet (2000) and translation method according to Newmark (1988). The data resources are volume one to ten of Crayon Shinchan comics. The data were analyzed with equivalent method and basic technique of sort direct decisive element. The result of this research shows that from 1.548 datas, nine categories of slang language are found and ora is thehighestfrequency of occurrence namely, 414datas (26,7%). There are 5 translation procedures are applied, 1.185 datas (76,55%) are literal translation procedure, 11 datas (0,7%) are borrowing procedure, 279 datas (18,02%) are modulation procedure, 47 datas (3,03%) are adaptation procedure, 26 datas (1,7%) are transposition procedure. While the orientation of the translation method is the source language.
Keywords: slang translation, translation procedure, translation method